(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
The transport of urea has been studied in a variety of epithelial tissues including the rumen, where carrier-mediated transport mechanisms have been reported. No such information concerning the transport of urea in the omasum is known. We have therefore carried out this study to characterize the transport mechanism of urea across the isolated omasum epithelium in sheep. This study was conducted under short circuit condition using conventional Ussing-chamber technique on 42 pieces of omasal epithelial tissues isolated from 5 sheep. Tissues bathing buffer solutions contained a mixture of antibiotics and the urease inhibitor phenylphosphorodiamidate (PPD). Our results show significant correlation (r2 = 0.85) between the transepithelial conductance ( Gt ) and the serosal to mucosal urea flux rates ( sm J ). Moreover, mucosal application of the actin cytoskeleton inhibitor cytochalasin D (10µM) significantly (p<0.05) increased both the tissue conductance ( Gt ) and the serosal to mucosal ( sm J ) flux rates of urea. However, reducing the mucosal pH from 7.4 to 6.4 did not induce a significant effect on the bidirectional urea flux rates across the omasum epithelium. The results indicate that transport of urea across the omasum epithelium involves a passive paracellular pathway mechanism. Key words: Sheep; Omasum; Urea; Cytochalasin D